QPVA-Based Electrospun Anion Exchange Membrane for Fuel Cells - Asep Muhamad Samsudin; Viktor Hacker (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The anion exchange membrane is one of the core components that play a crucial and inseparable role in alkaline anion exchange membrane fuel cells. Anion exchange membranes (AEMs) were prepared from quaternary ammonium poly(vinyl alcohol) (QPVA) by an electrospinning method. QPVA was used both as material for electrospun fiber mats and as filler for the inter-fiber void matrix. The objective of this work is to investigate the influence of the inter-fibers void matrix filler concentration on the properties and performance of eQPVA-x AEMs. FTIR spectra were used to identify the chemical structures of the AEMs. The primary functional groups of PVA and quaternary ammonium-based ion conducting cation were detected. The surface morphology of QPVA nanofiber mats and eQPVA-x AEMs was observed using SEM. Electrospun nanofiber structures of QPVA with an average size of 100.96 nm were observed in SEM pictures. The ion exchange capacity, swelling properties, water uptake, and OH-ions conductivity were determined to evaluate the performance of eQPVA-x AEMs. By incorporating the QPVA matrix of 5 wt.% concentration, the eQPVA-5.0 AEMs attained the highest ion exchange capacity, water uptake, swelling properties, and OH− conductivity of 0.82 mmol g−1, 25.5%, 19.9%, and 2.26 m×s cm−1, respectively. Electrospun QPVA AEMs have the potential to accelerate the development of alkaline anion exchange membrane fuel cells.